Strategies to improve the retention of health care workers in rural clinics of the Capricorn District, Limpopo Province - Mola, K. J. (My University, 2018)
Introduction and background The shortage of human resources in rural areas remains a crisis, especially in subSaharan Africa, affecting rural primary health centres. The purpose of this study was to identify and describe factors influencing the retention of health care workers in rural clinics, in order to develop strategies to improve retention in rural clinics. Methodology A quantitative research method and descriptive design was used in this study. The population was professional nurses and operational managers in rural clinics. Simple random sampling was used to select the clinics, the professional nurses and operational managers. The sample size were 210 professional nurses and operational managers. Only 170 professional nurses and operational managers participated in the study. Data were collected using a questionnaire, and all ethical principles were adhered to. The data was analysed using SPSS version 22.0. Results The study revealed that there are complex interconnecting factors that affect retention. It was further revealed that age is the core factor affecting retention (P= 0.001) with 19 (100%) of those aged < 30 years intending to leave rural practice. Furthermore, more than half of the respondents 118 (87.06%) were dissatisfied with the salary they earned. Only 1 (0.6%) of the respondents had a masters’ degree. Conclusion It is therefore concluded that both financial and non-financial incentives such as education, improving working conditions and relationship with colleagues needs to be incorporated in order to improve nurse retention. Key words: Retention, migration, rural health care workers, job satisfaction
Thesis (M.A. (Nursing Science)) --University of Limpopo, 2018
Keywords: Migration; Rural health; Care workers; Job satisfaction; Rural nursing; Rural health services; Nurses - Job satisfaction